Co-combustion, co-densification, and pollutant emission characteristics of charcoal-based briquettes prepared using bio-tar as a binder. (1st March 2021) - Cong, Hongbin; Yao, Zonglu; Mašek, Ondřej; Meng, Haibo; Sheng, Chenxu; Wu, Yunong; Zhao, Lixin
Highlights: Charcoal-based briquettes prepared using bio-tar as a binder were proposed. Charcoal improved the combustion characteristics of semi-coke. Addition of bio-tar enhanced the physical stability of charcoal-based briquettes. Effects of bio-tar addition on pollutant emission were controlled by hydrated lime. Abstract: In this study, charcoal-based briquettes prepared using bio-tar as a binder are proposed as a substitute for conventional coal in rural China; furthermore, the fuel properties of the blends of charcoal, semi-coke, and bio-tar and the co-densification and pollutant emission characteristics of charcoal-based briquettes are investigated. The addition of charcoal improved the heating value and combustion index; however, the addition of a small amount of bio-tar did not have any significant effect on the fuel properties of the charcoal and semi-coke blend. The blending of charcoal and semi-coke with a mass ratio of 1:1 increased the integrated combustion characteristics from 7.73 × 10 −12 (only semi-coke) to 16.92 × 10 −12  K −3 min −2 . Results of the co-densification experiments suggest that the bio-tar effectively improved the physical stability of charcoal-based briquette. By increasing the addition of bio-tar from 0 to 9 wt% at the densification temperature of 20 °C, the strength compaction and drop resistance increased by 8.6% and 13.9%, respectively. Increasing the densification temperature from 20 to 50 °C resulted in negative effects on mechanical strength. Pollutant emissions were observed during the ignition, stable combustion, and burnout phases of the stove. The bio-tar addition had distinct negative influences, increasing the total suspended particle and VOC emissions, which could be effectively weakened or eliminated by adding 3 wt% of hydrated lime. Herein, the applied chain and technical chain of charcoal-based briquettes are summarized. The study provides technical support for the industrial application of charcoal-based briquettes in rural China, with replication potential elsewhere.